PERTUMBUHAN SEMAI SAGA (Adhenanthera pavonina L) PADA BERBAGAI DOSIS KOMPOS KOTORAN AYAM - Darhana, Darhana; Wardah, Wardah; Umar, Husain; Rahmawati, Rahmawati (Universitas Tadulako, 2020)
Adhenanthera pavonina L is a multipurpose Tree Species Because Almoust tree species because almost all parts of the plant can be used and has high economi value. In supporting the develoment of adhenanthera pavonina L plants, quality seeds are needed in supfficient quantities and on time. The objektive 0f this research is to find out the effect of chicken manure compost on growth of Adhenanthera pavonina L seedling. This research was conducted for 4 months from April to july 2019 at the BPDS palu-poso , Tadulako University Palu. Anlalysis of compost content was carried out at soil science laboratory of agricultural faculty tadulako university palu. This research used a completely randomized design (CRD) method consisting of four treatments namely :k0= 1000g soil without compost, K1 =1000g soil :50g chicken manure compost, K2= 1000g soil:100g chicken manure compost, K3=1000g soil :150g chicken manure compost. Based on the resulst of the reserch show that soil treatment and chicken manure compost do not have a significant affect on height increase, number of leaves, and root dry weight, and root wet weight. The best Adhenanthera pavonina L plant growth is the treatment of K1= 1000g soil : 50g chicken manure compost with average plant heigt (3,71cm), plant diameter (1,46mm), number of leaves (2,37 strands) crown wet weight (4,22g), crown dry weight 91,24g), and root wet weight (1,15g) and seed quality index (0,13). The treatment of K1= 1000g: 50g chicken manure compost gives a better aeefect compared to other treaments.Keywords: growth, compost, Adhenanthera pavonina L